2021
DOI: 10.3389/fnut.2021.727467
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Effect of Lactobacillus fermentum CQPC04-Fermented Soy Milk on D-Galactose-Induced Oxidative Aging Mice

Abstract: The aim of this study is to evaluate the changes in soy isoflavones and peptides in soy milk after lactic acid bacterial fermentation, and explore the positive effects of fermented soy milk on an oxidative aging mouse model induced with D-galactose. We found that free soybean isoflavones and peptides increased after soy milk was fermented by Lactobacillus fermentum CQPC04. The in vivo results indicated that L. fermentum CQPC04-fermented soy milk enhanced the organ index of the liver and spleen, and improved th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…delbrueckii TUA4408L in pigs enhanced the resistance to pathogenic Escherichia coli infection and reduced pathogen-associated inflammatory damage in the intestinal mucosa (Suda et al 2022). Another investigation observed that fermentation of soymilk with Lactobacillus fermentum CQPC04 significantly increased the isoflavones content which was associated with attenuation of oxidative damage and improved indices of antioxidant defenses in serum, liver, and brain tissues of mice in a d-galactose-induced model of accelerated aging (Zhou et al 2021). In addition, the effectiveness of probiotic fermented soymilk consumption in the attenuation of antibiotic-associated gut microbial dysbiosis in mice has also been observed (Dai et al 2019).…”
Section: Fermented Soymilkmentioning
confidence: 98%
“…delbrueckii TUA4408L in pigs enhanced the resistance to pathogenic Escherichia coli infection and reduced pathogen-associated inflammatory damage in the intestinal mucosa (Suda et al 2022). Another investigation observed that fermentation of soymilk with Lactobacillus fermentum CQPC04 significantly increased the isoflavones content which was associated with attenuation of oxidative damage and improved indices of antioxidant defenses in serum, liver, and brain tissues of mice in a d-galactose-induced model of accelerated aging (Zhou et al 2021). In addition, the effectiveness of probiotic fermented soymilk consumption in the attenuation of antibiotic-associated gut microbial dysbiosis in mice has also been observed (Dai et al 2019).…”
Section: Fermented Soymilkmentioning
confidence: 98%
“…Having a-glucosidase inhibitory activity [106][107][108][109][110][111] . Having the ability to improve glucose homeostasis in mouse 56 Fermented soy milk ↑: genus Bifidobacterium, Collinsella, and Prevotella in human ↓: unclassified genera of the families Ruminococcaceae and Lachonospiraceae in human 57,58 Having antioxidant effect 29,112,113 and anti-inflammatory effect 29 . Having the ability of modulating GLUT4 expression in muscles 114 Tempeh ↑: phylum Actinobacteria in Zebrafish; Bacteroidetes, Firmicutes, Clostridium leptum in rat; Bacteroides fragilis, Bifidobacterium, Lactobacillus, Escherichia coli, Enterococcus, and Akkermansia in human ↓: phylum Proteobacteria in Zebrafish [59][60][61][62] Having antioxidant effect [119][120][121][122]…”
Section: Douchimentioning
confidence: 99%
“…The reaction was performed using a quantitative PCR instrument under the following conditions: 60 seconds at 95°C, 15 seconds at 95°C for 40 cycles, 30 seconds at 55°C, and 35 seconds at 72°C. Finally, the target gene was analyzed using the 2 −ΔΔC method with GAPDH as the internal reference [11,12].…”
Section: Measurement Of Mrna Expression In Mouse Ankle Joint Tissuementioning
confidence: 99%